2017
DOI: 10.1039/c7ta05679f
|View full text |Cite
|
Sign up to set email alerts
|

Interior multi-cavity/surface engineering of alginate hydrogels with polyethylenimine for highly efficient chromium removal in batch and continuous aqueous systems

Abstract: Highly recyclable multi-core@shell-like HS-PDA@PEI-SA@PEI beads with interior/surface accessible polyethylenimine have been designed for ultrahigh Cr(vi) sorption performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 164 publications
(53 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…In which, peaks at 23.5, 29.6, 31.9, 36.2, 39.4, 43.2, and 57.6°, are indexed to the (012), (014), (006), (110), (116), and (122) crystal planes of CaCO 3 , respectively (JCPDS, no. 00‐005‐0586) . Obviously, due to the insoluble character of calcium carbonate, there are no other kinds of calcium, and the solubility product can be expressed in Eqn (3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In which, peaks at 23.5, 29.6, 31.9, 36.2, 39.4, 43.2, and 57.6°, are indexed to the (012), (014), (006), (110), (116), and (122) crystal planes of CaCO 3 , respectively (JCPDS, no. 00‐005‐0586) . Obviously, due to the insoluble character of calcium carbonate, there are no other kinds of calcium, and the solubility product can be expressed in Eqn (3).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some extra cobalt solution was produced in the fabrication process of SA/N−Co x O y , thus, it is high time to find a valuable and feasible method to take a full use of the waste solution. Recently, scholars and our team found that amino groups can effectively anchor multivalent ions . One of the agents is polyethylenimine (PEI), which is often used to modify the materials due to its metal chelation properties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations